Dominasi Korean Hallyu Dalam Konteks Strukturasi Di Industri Budaya - Safira Hasna (Jurnal Komunikasi, 2021)
The popularity of Korean dramas and songs triggers the dominance of Korean Hallyu internationally in various parts of the world. One of the factors which triggers this dominance is the Kpop Bangtan Sonyeodan boy band (BTS). BTS does not only create songs that are massive and standard but also  has a meaning that makes them won a number of international awards. The objective of this paper is to analyze the dominance of Korean hallyu especially Korean boy band BTS as a pioneer of the Asian music industry internationally using structuration theory in the context of the cultural industry by using the literature review method, this is  to describe a number of findings related to the cultural industry and structuration. As a result, BTS as an agent  become an active participant who can reproduce the social system by referring to social actions that ultimately produce a social structure, BTS as an active agent can become a creative labour in the cultural industry by creating works that are not only profit-oriented but combines with the creativity which able to deliver messages through its music, as pioneer of Korean artists internationally.